PENGARUH TEKNIK EFFLEURAGE MASSAGE TERHADAP NYERI AFTERPAINS PADA IBU NIFASMULTIPARA DI BPM WANTI DAN BPM SARTIKA DI KOTA MEDAN TAHUN 2020 - Sitorus, Friska; Harianja, Ester (JURNAL HEALTH REPRODUCTIVE, 2020)
Post-partum mothers often experience changes both physiologically and psychologically, one of which is a change in the body's reaction due to uterine contractions. The intensity of uterine contractions increases after delivery which causes pain and makes the mother uncomfortable. Many experienced pain disorders during the puerperium even in uncomplicated normal delivery. This causes discomfort in the mother, especially in the abdominal area due to uterine contractions called afterpains. This massage therapy can minimize and even suppress pain with minimal side effects or even no side effects, one of which is using effleurage massage techniques. This study aimed to determine the effect of effleurage massage technique on afterpains pain in multiparous postpartum mothers. This research is a quasi experiment or quasi-experiment. The design of this study used a one group pre-test-post-test design. The results showed that the pain intensity in postpartum mothers before the effleurage massage technique experienced moderate pain, namely 73.3%, and mild pain, namely 26.7%, after effleurage massage 83.3% experienced mild pain and did not experience pain, namely 16 7%. The results of this study concluded that the effleurage massage technique can be used as a non-pharmacological therapy that can overcome the afterpains pain in postpartum mothers, thereby reducing the pain felt by the mother and will make the mother feel comfortable.